2016
DOI: 10.1080/17470218.2015.1038571
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and Feature Binding in Visual Working Memory: The Role of Presentation Time

Abstract: A large body of research has clearly demonstrated that healthy ageing is accompanied by an associative memory deficit. Older adults exhibit disproportionately poor performance on memory tasks requiring the retention of associations between items (e.g., pairs of unrelated words). In contrast to this robust deficit, older adults' ability to form and temporarily hold bound representations of an object's surface features, such as colour and shape, appears to be relatively well preserved. However, the findings of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 59 publications
11
47
0
1
Order By: Relevance
“…These results support previous findings obtained in separate studies and showing agerelated short-term binding difficulties for item-item and item-context relational associations (Borg et al, 2011;Chen & Naveh-Benjamin, 2012;Cowan et al, 2006;Fandakova et al, 2014;Mitchell, Johnson, Raye, Mather, et al, 2000;Olson et al, 2004), but no evidence for an associative deficit for colour-shape and colour-colour conjunctive associations (Brockmole & Logie, 2013;Brockmole et al, 2008;Brown & Brockmole, 2010;Brown et al, 2017;Isella et al, 2015;Parra et al, 2009;Read et al, 2016;Rhodes et al, 2016Rhodes et al, , 2017. Importantly, the current study demonstrates this differential age effect in a task in which all aspects of the procedure were identical across tasks except how objects and colours were related to each other, supporting the idea that this is the nature of the associations which is critical.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results support previous findings obtained in separate studies and showing agerelated short-term binding difficulties for item-item and item-context relational associations (Borg et al, 2011;Chen & Naveh-Benjamin, 2012;Cowan et al, 2006;Fandakova et al, 2014;Mitchell, Johnson, Raye, Mather, et al, 2000;Olson et al, 2004), but no evidence for an associative deficit for colour-shape and colour-colour conjunctive associations (Brockmole & Logie, 2013;Brockmole et al, 2008;Brown & Brockmole, 2010;Brown et al, 2017;Isella et al, 2015;Parra et al, 2009;Read et al, 2016;Rhodes et al, 2016Rhodes et al, , 2017. Importantly, the current study demonstrates this differential age effect in a task in which all aspects of the procedure were identical across tasks except how objects and colours were related to each other, supporting the idea that this is the nature of the associations which is critical.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the use of verbally accessible objects and colours may have allowed verbal recoding of the stimuli. This should not have strongly influenced the results because previous work showed the same pattern of equal age effect on feature and conjunctive binding short-term memory with difficult to verbalize materials (Brockmole et al, 2008, Experiment 2;Isella et al, 2015), meaningful shapes with articulatory suppression (Brockmole et al, 2008, Experiment 1;Brown & Brockmole, 2010;Brown et al, 2017;Rhodes et al, 2016) and meaningful shapes without articulatory suppression (Brockmole & Logie, 2013;Read et al, 2016). Yet, future work should confirm 19 our findings either with meaningless materials or with articulatory suppression.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Rhodes and colleagues argued for a distinction between binding of extrinsic features (i.e., linking of distinct items or contextual features accompanying an item) and binding of features that define the intrinsic characteristics of an object (i.e., within-item binding) (see also Allen et al, 2013; Rhodes et al, 2015). Binding objects' intrinsic features appears to be an automatic process (Allen et al, 2006, 2009; Karlsen et al, 2010; but see Shen et al, 2015; Gao et al, 2017) that is largely spared by age (Parra et al, 2009b; Brown and Brockmole, 2010; Isella et al, 2015; Rhodes et al, 2015; Read et al, 2016; Brown et al, 2017). In contrast, binding extrinsic features requires more cognitive resources (e.g., associative functions of the medial temporal lobe), which appear to be more susceptible to the effects of age (Mitchell et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This function remains preserved across the life span (Parra, Abrahams, Logie, & Della Sala, 2009;Rhodes, Parra, & Logie, 2015), and does not rely on the hippocampus (Parra, Della Sala, Logie, & Morcom, 2014;Parra, Fabi, Luzzi, Cubelli, Hernandez et al, 2015). Liang et al (2016) showed that relational functions carried out during VSTM also decline in pre-symptomatic cases of FAD.…”
Section: Memory At the Boundaries Between Normal And Abnormal Ageingmentioning
confidence: 95%